Traditional Uses, Pharmacological Effects, and Molecular Mechanisms of Licorice in Potential Therapy of COVID-19 - Zhang, Qian-hui; Huang, Hao-zhou; Qiu, Min; Wu, Zhen-feng; Xin, Zhan-chang; Cai, Xin-fu; Shang, Qiang; Lin, Jun-zhi; Zhang, Ding-kun; Han, Li (Frontiers in Pharmacology, 2021)
Background: Since the emergence of the novel coronavirus disease (COVID-19), it has become one of the most serious infectious diseases globally, and the epidemic situation is extremely difficult. Licorice, as traditional herbal medicine, has several pharmacological effects, such as anti-inflammatory, detoxification, antibacterial, antitussive and immunomodulatory effects. Relevant literature and clinical studies show that licorice could be used as a potential medicine to prevent and treat COVID-19. These studies provide a good reference point for exploring the mechanism of licorice can be useful to develop an alternative medicine for treating COVID-19. Purpose: With the increasing number of cases of COVID-19. Nevertheless, there is still no drug to treat COVID-19. Therefore, it must provide a reference for new drug development and clinical treatments for COVID-19. Methods: We reviewed the potential pharmacological effects and mechanism of action of licorice to assist in the treatment of COVID-19, and discussed the feasibility of using it for treating COVID-19. Results: Recent studies have revealed the possible binding sites present on SARS-CoV2 and studied their interactions with licorice, its active substances, especially glycyrrhizin, and liquiritin have shown an important interaction with the SARS-CoV2 proteins, such as the ACE2 receptor. Studies further emphasize the activity of these active substances against COVID-19. Conclusion: This review summarizes the available reports and evidence which support the use of licorice as potential candidates in the treatment of COVID-19.